EXAMINING THE EFFECT OF ETHICAL LEADERSHIP ON GREEN WORK OUTCOMES: A MODERATED MEDIATION ANALYSIS - Hameed, Ahmed Abdul; Anjum, Zafar-uz-Zaman; Rasheed, Maria; Khalid, Imran; Umar, Muhammad; Gill, Aasim Naimat (The journal of contemporary issues in business and government, 2021)
The current study examines the direct effect of ethical leadership (EL) on employee green commitment (EGC) and the indirect effect on employee green innovative work behavior (EGIWB). It also tested the moderating effect of employee green knowledge (EGK) in the relationship between EL and EGC. Data were collected from 359 employees working in the manufacturing sector of Pakistan. Time lagged and conveniences sampling technique was adopted. The statistical results showed that EL was positively related to EGC. EGC enhances the EGIWB. Moreover, results showed that EGK moderates the relationship between EL and EGC. Such that employees having high green knowledge have more inclination towards green commitment. The results also showed that EL enhances EGIWB via EGC. Moderated mediation results also showed that EGK strengthens the indirect relationship between EL and EGIWB. Result depicted that employee having high green knowledge shows more green innovative work behavior via increased green commitment. The study brings important practical implications for top and middle managers and addresses their concerns about green practices and green innovations in their firms.